Sharing health data to create value: A systematic review - Zonoobi, Mojtaba; Elahi, Shaban; Khansari, Mohammad; Hassanzadeh, Alireza; Sahib, Tahereh (Researcher Bulletin of Medical Sciences, 2024)
Objective: With the introduction of digital crypto currency, the worth of data has been obvious to everybody. Of course, this research is in the sphere of medicine. The goal of this research is to perform a comprehensive evaluation of studies in the area of health information system data sharing and secondary uses of health data, with the goal of generating value in multiple dimensions by sharing these data. Material & Methods: The researchers used the intelligent Web of science and IEEE search engines to conduct a systematic evaluation of English-language keyword searches. Two tactics have been studied in this respect, one using keywords related to "health data value" and the other using terms linked to "health data sharing." Results: Although several studies have suggested solutions for decreasing obstacles to health information system data sharing, they have often simply addressed the problem, according to one criticism of the papers examined. The sharing barrier has no remedy, and its relevance is simply emphasized. Conclusion: It was discovered that not all of the successful components of data sharing, particularly data from health information systems, were addressed in the evaluated studies.